La acción de Benedicto XVI en la crisis del Líbano - Corral, Carlos; Priego, Alberto (UNISCI Discussion Papers, 2007)
The last crisis between Hezbollah and Israel has left a great track of destruction and death among the population. Nevertheless, the figure of Benedict XVI has emerged in the middle of this distressing scene. His moderate and pacific performance confirms two factors that are taking place in the International Community. On the one hand, the increase of the importance of the individual in the international relations. On the other, the politicization of religion.